Role of laparoscopy as a minimally invasive procedure in treatment of ruptured uterine scar during second‐trimester induction of abortion. Issue 4 (23rd December 2015) - Zheng, Yanmei; Jiang, Qiaoying; Lv, Ya‐er; Liu, Feng; Yang, Liwei
Abstract: Uterine rupture is an uncommon complication following termination of pregnancy and is usually accompanied by severe lower abdominal pain and shock caused by intra‐abdominal hemorrhage. Laparotomy should be carried out promptly in order to repair the uterus or even to resect the uterus. Here we present a case of uterine rupture of a scarred uterus, which occurred during a second‐trimester induced abortion. The patient was successfully treated by laparoscopy with the help of laparoscopic ultrasound. This case suggests an alternative, effective approach to the diagnosis and treatment of uterine rupture.